2012
DOI: 10.1177/1367493511420186
|View full text |Cite
|
Sign up to set email alerts
|

The daily patterns of time use for parents of children with complex needs

Abstract: The aim of this systematic review was to critically examine the research that quantifies and describes the daily patterns of time use by parents of children with complex needs. Four electronic databases were searched. A total of 32 studies (30 peer-reviewed journal articles and two theses) met the inclusion criteria. Three key findings emerged from the review: (a) Parents of children with complex needs carry a significant caregiving burden that often does not reduce as the age of the child increases, (b) super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 54 publications
6
145
1
3
Order By: Relevance
“…[5][6][7][8] In addition to the significant out-of-pocket expense of these therapies, substantial time is spent learning to navigate the service delivery and eligibility system, coordinating care, advocating for coverage with insurance companies, and augmenting therapy with practice at home. 9,10 It is not that parents overlook their other children who are typically developing. Parents worry that they can't provide enough for all their children.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] In addition to the significant out-of-pocket expense of these therapies, substantial time is spent learning to navigate the service delivery and eligibility system, coordinating care, advocating for coverage with insurance companies, and augmenting therapy with practice at home. 9,10 It is not that parents overlook their other children who are typically developing. Parents worry that they can't provide enough for all their children.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with parents of typically developing children, parents of children with special needs spend longer time in childcare activities (Crowe & Florez, 2006;McCann, Bull, & Winzenberg, 2012). One study found that mothers of children with a disability engaged in childcare activities on average 13.1 hours more per week than mothers of children without a disability (Crowe & Florez, 2006).…”
Section: Mothers' Experiences When There Is a Child With Asd In Theirmentioning
confidence: 99%
“…We chose these 14 activities from previous publications on time use of mothers of children with a disability (Gevir, Goldstand, Weintraub, & Parush, 2006;McCann et al, 2012). The fourteen activities listed in this study were (1) sleep, (2) grooming and personal hygiene, (3) meal preparations and clean up, (4) having a meal, (5) taking care of child, (6) travel time to and from school or work, (7) time spent at work, (8) personal leisure time, (9) house duties, (10) shopping, (11) having quiet time or down time, (12) visiting family/friends, (13) studying, and (14) voluntary work.…”
Section: Time Use Estimate Tablementioning
confidence: 99%
See 1 more Smart Citation
“…It therefore falls to health professionals to recognise the implications of any additional demands made (McCann, Bull, and Winzenberg 2012) and ensure adequate support and resources are available. Moreover, whilst it is important to recognise the value of parents' knowledge, there is still a need for information and education to support them to fulfil this role (Wolfendale 2002).…”
Section: Evolution Of Practicementioning
confidence: 99%